Social teachings of Catholic church and Islam - Sayadat, Mohammad Nazmus; Ushama, Thameem (IIUM Press, 2017)
This book examines Catholic social teachings from an Islamic perspective through investigating its history, development, and principles by analyzing from Islamic social teachings. It investigates the concept of the social teachings of the Catholic Church and their goals in contemporary societies. It provides the approaches of contemporary Muslim scholars towards understanding the social teachings of the Catholic Church. It employs the qualitative methodology focusing on documentary analysis of the original texts and materials. It starts with an overview of the research including objectives, research questions, scope and literature review. It provides an introductory analysis of Catholic social teachings with its theology and doctrines. It also presents the basic features of Catholic Church with the Church’s mission, nature and principles of Catholic social teaching from theological perspective. Chapter Three demonstrates the understanding of Islamic social teachings by studying the Islamic social order and its sources and the major principles of Islamic social teachings in line with the principles of Catholic social teachings. Chapter Four significantly examines and analyzes these two social teachings and tries to find out the similarities and differences from theoretical and practical perspectives and finally makes an Islamic critique. Chapter Five is the findings and conclusion of the present research where it is noted the significant differences of these two social teachings’ nature and objectives by studying the history and methodology of evangelization through Church activities. This study has arrived at the following conclusions: (i) Theoretically, Catholic social teachings and Islamic social teachings share the common social norms but they are much different when they come to belief and practice. (ii) The sources of Catholic social teachings have a great influence from the Church, thus humanistic, while Islamic social teachings are purely divine. (iii) Productive Muslim-Christian inter-religious dialogues and discussions are the major elements to promote peace and eradicate contemporary problems and obstacles which make these two religious followers away from each other, and to bring mutual respect, peace, faith and harmony for them in particular but humanity in general. Since Church works play a major role in Christianization and evangelizations, it is hoped that this research will help Muslims especially academics to understand the process of Christianization better and facilitate them to respond to the Catholic onslaughts.